1988
DOI: 10.1111/j.1476-5381.1988.tb10326.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diuretics on GABA‐gated chloride current in frog isolated sensory neurones

Abstract: Effects of three diuretics (furosemide, amiloride and α‐human atrial natriuretic polypeptide (α‐hANP)) on GABA‐activated chloride current (ICl) were investigated in frog isolated sensory neurones, following suppression of Na+, K+ and Ca2+ currents, by use of a ‘concentration‐clamp’ technique. Furosemide inhibited the GABA‐activated ICl in a non‐competitive manner and facilitated the inactivation phase, while amiloride inhibited the GABA response in a competitive manner, both inhibitions being concentration‐dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 23 publications
(24 reference statements)
2
12
0
Order By: Relevance
“…We found that amiloride inhibited the activity of recombinant GABARs of mammalian origin, confirming an earlier report with GABARs in frog sensory neurons (Inomata et al, 1988). Amiloride has also been shown to modulate the activity of neurotransmitter receptors, including the adenosine (Garritsen et al, 1990) and adrenergic receptors (Howard et al, 1987;Nunnari et al, 1987).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…We found that amiloride inhibited the activity of recombinant GABARs of mammalian origin, confirming an earlier report with GABARs in frog sensory neurons (Inomata et al, 1988). Amiloride has also been shown to modulate the activity of neurotransmitter receptors, including the adenosine (Garritsen et al, 1990) and adrenergic receptors (Howard et al, 1987;Nunnari et al, 1987).…”
Section: Discussionsupporting
confidence: 77%
“…The results of Inomata et al (1988) suggested that amiloride was a competitive antagonist at GABARs in frog sensory neurons. Therefore, we examined the effect of GABA concentration on inhibition of the ␣6␤3␥2L receptor by amiloride.…”
Section: Inhibition Of Gabamentioning
confidence: 82%
See 1 more Smart Citation
“…They all concluded that FM had a specific depressing effect on the receptor-operated opening of Cl--channels in these neurons. Inomata et al (1988) investigated the effects of FM on the GABA-activated chloride current (Ic1) of the isolated frog sensory neurons, using so called concen tration clamp method. They reported that FM inhibited the GABA-activated Ic1, in a non-competitive manner, and suggested that FM would act specifically on the open channel conformation of the GABA-gated Cl--channel and facilitate its inactivation.…”
Section: Effects Of Fm On the Cv-dependent Hyperpolarizing Responsesmentioning
confidence: 99%
“…Furthermore, guanidine compounds that modulate the acid-sensing ion channel influence Cys-loop receptor activity. The inhibitory effect of the diuretic amiloride, an acid-sensing ion channel antagonist, on GABA-A receptors was first reported in the frog sensory neurons (Inomata et al, 1988), and subsequent studies focused on amiloride in GABA-A abg receptors showed that the guanidine compound competitively antagonized the receptors with a 10-fold increased potency in GABA-A a6-containing receptors (Fisher, 2002). In the inhibitory glycine receptor, amiloride exhibited competitive antagonism in receptors expressed in rat spinal neurons and inferior colliculus (Li et al, 2003a,b;Tang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%